INTI AJARAN DALAM TEKS ĀTMABODHA: PERSPEKTIF TEOLOGI HINDU - Gupta, Gede Endy Kumara; Surada, I Made; Sena, I Gusti Made Widya (Pangkaja: Jurnal Agama Hindu, 2023)
The Ātmabodha is a sanskrit classic text written by Śaṅkarācārya containing the teachings on Ātman. The main purpose of the text is how to teach oneself to be able to experience Ātman through the knowledge of it and at the same time through this knowledge oneself can eliminate various forms of upādhi that have been covering up the true nature of the Self. The Ātmabodha is also a meditative text compiled in simple prose to make it easier for spiritual practitioners who read it to be used as a contemplative medium in receiving knowledge about Ātman. This paper aims to comprehensively analyze the essence of the teachings contained in the Ātmabodha. The perspective of Hindu theology will be the point of view in this paper, with the theory of structural semiotics and vedic hermeneutics to assist the analysis. Brahman, Ātma, upādhi, and the pursuit of realization of Brahman (Mokṣa) are central themes in the analysis of the Ātmabodha.